Comportamiento clínico y diagnóstico de laboratorio de la Lepra en Latinoamérica. - Lima Quishpe, Sheyla Dayana (2024)
Hansen's disease, caused by Mycobacterium leprae or Mycobacterium lepromatosis, persists as a public health challenge, especially in invulnerable areas. This research was carried out using a bibliographic review to gather scientific information on the clinical behavior and laboratory diagnosis of this pathology in Latin America. A descriptive, documentary, and non-experimental, retrospective study, where 30 scientific articles were reviewed, and only 23 were selected, using inclusion and exclusion criteria. The information was searched in databases such as Infomed, Mip salud, Repositories, Pubmed, Scielo, Plos Magazine, Medigraphic, Elsevier, Dialnet, Rev. Argentina, EBSCO, Mefagram, Manual, Wired, and Bvsalud. With the analysis and discussion of the different authors, the proposed objective was achieved, in which it was evidenced that the most frequent clinical forms of presentation of leprosy were tuberculoid and lepromatous forms. Skin lesions, peripheral nerve involvement, and physical disability were the most common clinical manifestations reported. Physical examination, biopsy, and bacilloscopy were identified as the most used diagnostic methods. The latter has certain limitations due to its low sensitivity in cases with few bacilli, however, the Polymerase Chain Reaction, which is a rapid and accurate method for early detection of these mycobacteria, was used by most researchers. Health professionals with these findings can reach a timely diagnosis and treatment, which will improve patients' quality of life.